2012
DOI: 10.1152/ajpendo.00421.2012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal androgen excess reduces placental and fetal weights, increases placental steroidogenesis, and leads to long-term health effects in their female offspring

Abstract: -Victorin E. Maternal androgen excess reduces placental and fetal weights, increases placental steroidogenesis, and leads to long-term health effects in their female offspring. Am J Physiol Endocrinol Metab 303: E1373-E1385, 2012. First published October 9, 2012 doi:10.1152/ajpendo.00421.2012.-Here, we tested the hypothesis that excess maternal androgen in late pregnancy reduces placental and fetal growth, increases placental steroidogenesis, and adversely affects glucose and lipid metabolism in adult female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 54 publications
9
79
1
1
Order By: Relevance
“…These results are in line with a recent study in the offspring of female PNA mice that used liquid chromatography tandem (LC)-MS/MS (29). In contrast, higher circulating testosterone has previously been reported in female rat PNA offspring (12). This discrepancy may be a result of the higher doses of maternal testosterone (5 mg) used in the previous study compared with the present study (0.5 mg).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in line with a recent study in the offspring of female PNA mice that used liquid chromatography tandem (LC)-MS/MS (29). In contrast, higher circulating testosterone has previously been reported in female rat PNA offspring (12). This discrepancy may be a result of the higher doses of maternal testosterone (5 mg) used in the previous study compared with the present study (0.5 mg).…”
Section: Discussionsupporting
confidence: 90%
“…One possible explanation may be an effect of maternal testosterone exposure on the organization of the brain, which may permanently alter brain morphology and subsequently give rise to altered behavioral responses (27). Another possibility is that high testosterone in the mother alters steroid production in the placenta (12), which may affect the fetus. We found that placental weight was reduced in androgenized rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slides were rinsed in distilled water for 5 min and counterstained with Mayer's hematoxylin (#01820; Histolab, Sweden) before mounting with medium containing glycerol (50%) and gelatin (7%). The samples were classified into positive (+), possible early (+/−), and negative (−) fatty liver (61). Adipocyte size measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Their role seems to be multifactorial and is believed to be implicated in multiple steps of hepatic physiology. Their impact may be apparent even in intrauterine stages of life by modifying liver metabolism and signaling [24,25].…”
Section: Discussionmentioning
confidence: 99%